若(a2+b2-3)*(a2+b2+3)=7,则a2+b2=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 12:34:23
若(a2+b2-3)*(a2+b2+3)=7,则a2+b2=若(a2+b2-3)*(a2+b2+3)=7,则a2+b2=若(a2+b2-3)*(a2+b2+3)=7,则a2+b2=(a2+b2-3)*
若(a2+b2-3)*(a2+b2+3)=7,则a2+b2=
若(a2+b2-3)*(a2+b2+3)=7,则a2+b2=
若(a2+b2-3)*(a2+b2+3)=7,则a2+b2=
(a2+b2-3)*(a2+b2+3)=7
(a2+b2)^2-9=7
则(a2+b2)^2=16
则a2+b2=4
假设a2+b2=x 原式=(x-3)*(x+3)=7
一元二次方程求解 x^2=7 x=根号7 x=-根号7
所以a2+b2=正负根号7
若(a2+b2-3)*(a2+b2+3)=7,则a2+b2=
3b2次方-(a2次方+b2次方)-b2次方
(3a2-3ab+2b2)+(a2+4ab-2b2)=4a2+ab+b2
2a-3b/b2-a2 -a+3b/a2-b2 +a+2b/a2-b2
2a-3b/b2-a2 -a+3b/a2-b2 +a+2b/a2-b2
(a2+b2)(a2+b2-3)=10求a2+b2的值
(a2+b2)(a2+b2-3)-4=0,求a2+b2的值
若a2+b2+c2
a2+b2
已知a2+AB=3,AB-B2= -2求a2+b2,a+2ab-b2
3(a2-2ab)-(-ab+b2)+(2ab+b2)
(a2+b2)(a2+b2-3)=10 求(a2+b2)的值 为什麼这样解!
已知a2++ab=3,ab+b2=1,试求a2+2ab+b2,a2-b2的值
如果a2+ab=4,ab+b2=-1,那么a2-b2=?,a2+3ab+2b2=?
因式分解a2-3ab+2b2
化简 3a2-ab/3a2+5ab-2b2
若a2>b2,则a
已知a≠b,若a2+3a-7=0,b2+3b-7=0,则a2+b2